Non-smooth model and numerical analysis of a friction driven structure for piezoelectric motors. (May 2017) - Liu, Weiting; Zhou, Maoying; Ruan, Xiaodong; Fu, Xin
Abstract: In this contribution, typical friction driven structures are summarized and presented considering the mechanical structures and operation principles of different types of piezoelectric motors. A two degree-of-freedom dynamic model with one unilateral frictional contact is built for one of the friction driven structures. Different contact regimes and the transitions between them are identified and analyzed. Numerical simulations are conducted to find out different operation modes of the system concerning the sequence of contact regimes in one steady state period. The influences of parameters on the operation modes and corresponding steady state characteristics are also explored. Some advice are then given in terms of the design of friction driven structures and piezoelectric motors. Abstract : Highlights: We develop a simplified model for a previously proposed piezoelectric motor. Different operation modes are identified in terms of the constituent contact regimes. Influence of drive frequency on system characteristics is studied. Influence of coefficient of friction on system characteristics is studied. Influence of initial tilt angle of the rod on system characteristics is studied.